Design and synthesis of pyridazinone-substituted benzenesulphonylurea derivatives as anti-hyperglycaemic agents and inhibitors of aldose reductase – an enzyme embroiled in diabetic complications. (1st November 2016) - Yaseen, Raed; Pushpalatha, H.; Reddy, G. Bhanuprakash; Ismael, Ameer; Ahmed, Ayad; Dheyaa, Alhamza; Ovais, Syed; Rathore, Pooja; Samim, Mohammed; Akthar, Mymoona; Sharma, Kalicharan; Shafi, Syed; et al.
Abstract: Thirty new aryl-pyridazinone-substituted benzenesulphonylurea derivatives (I –XXX ) were synthesized and evaluated for their anti-hyperglycaemic activity in glucose-fed hyperglycaemic normal rats. Twenty-three compounds (III –XI, XIV –XVII, XIX –XXIV, XXVI andXXVIII –XXX ) showed more or comparable area under the curve (AUC) reduction percentage (ranging from 21.9% to 35.5%) as compared to the standard drug gliclazide (22.0%). On the basis of docking results, 18 compounds were screened for their in vitro ability to inhibit rat lens aldose reductase. Ten compounds (III –VI, XII, XVI –XVIII, XXI andXXVII ) showed ARI activity with IC50 ranging from 34 to 242 μM. Out of these, two compounds IV and V showed best ARI activity which is comparable with that of quercetin. As a result, two compounds (IV and V) possessing significant dual action (anti-hyperglycaemic and aldose reductase inhibition) were identified and may be used as lead compounds for developing new drugs.